Potency of Herpetofauna in Tanjung Puting National Park, SPTN I Pembuang Hulu and SPTN III Tanjung Harapan - Muhtianda, Iman Akbar; Perdana, Anxious Yoga; Januarisa, Dela Valenia (Universitas Bengkulu, 2024)
Indonesia is an archipelago country located in Southeast Asia. It has high numbers of species in terms of biodiversity and ecosystem variations. Amphibians and reptiles also exist in the ecosystem of Indonesia. Herpetology is a discipline of zoology that focuses on amphibians and reptiles (herpetofauna). Amphibians and reptiles do not share the same taxonomic group, but they are studied together because they share similar physiological character hence it influences their behavior and metabolism, so they would study with similar method in one discipline. Amphibians and reptiles are widespread across the globe, and they play various roles in the ecosystem. This survey was conducted in morning at 6:00 to 9:00 and in evening at 18:00 to 22:00 at Resort Pondok Ambung SPTN I Pembuang Hulu, Pos Jaga Sungai Buluh Besar, and Pos Jaga Sungai Buluh Kecil Resort Teluk Pulai SPTN III Tanjung Harapan, Taman Nasional Tanjung Puting, between 2020 – 2023. The method was Visual Encounter Survey combined with Road Cruising and/or River Cruising. Herpetofauna photo was taken, and the species was identified by its morphological character based on the field guide. The result is morphology character and protection status description. The species encountered consist of five species of amphibians: Pseudobufo subasper, Polypedates colletti, Polypedates macrotis, Leptobrachium abbotti, Hylarana erythraea, and Pulchrana baramica. Eight species of reptiles: Tomistoma schlegelii, Crocodylus porosus, Draco cornutus, Ptychozoon kuhlii, Varanus salvator, Dendrelaphis sp., Fowlea piscator, and Malayopython reticulatus.